EXPLORING THE MOST INNOVATIVE AI APPLICATIONS IN EDUCATION (Educator Insights: Journal of Teaching Theory and Practice, 2025)
Artificial Intelligence (AI) is reshaping the world of education with its fresh and innovative applications, introducing automation, customization and engagement in learning. The integration of AI in education has introduced teachers and students to a new era where learning is not confined to the pages of textbooks but is adapted to each individual’s unique pace, style, and needs.